Analysis of Critical Reading Skills of Sixth Grade Elementary School Students - Aden Muhammad Taupik; Karantiano Sadasa Putra; Yusi Ardiyanti; Nursyifa Pebriani; Lulu Fitria Ramadhan (Publikasi Pendidikan, 2026)
The purpose of this literature review research is to describe the critical reading skills of sixth grade elementary school students and to identify factors that can cause low critical reading skills. The method used in this study is a literature review with a qualitative approach to analyzing the critical reading skills of elementary school students. The results of this study indicate that critical reading skills are high-level thinking that requires students to compare and evaluate a text logically. This gap in critical reading skills is experienced by students who tend to be at the literal reading level in distinguishing facts and opinions and distinguishing the meaning contained in the text. These problems tend to be caused by internal and external factors. Internally, low reading interest and critical thinking skills of students. While externally, the use of conventional learning methods results in a lack of innovation. Solutions to overcome the above problems can be overcome by using Wondershare Quiz Creator media and active learning models such as the Inquiry Model and the Echo Model and strengthened by a guided lantern program.